Critical Issues: A Decade of Local Politics Research in Global Bibliometric Analysis - Rosmita Rosmita; Sarmito Sarmito; Ade Fristy Syahara (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2025)
This study maps and diagnoses global research trends in local politics using bibliometric methods to clarify how the field has evolved and where it is heading. Its novelty lies in combining VOSviewer network visualization with Bibliometrix performance and thematic analyses on a large Scopus-indexed corpus, enabling an integrated view of intellectual structure, collaboration patterns, and emerging topics. The urgency of this work stems from the growing policy relevance of local governance amid decentralization pressures, democratic backsliding, and demands for accountability and citizen participation, which require evidence-based synthesis beyond fragmented case studies. We conducted a qualitative literature study supported by bibliometric analysis of 1,366 documents published between 2014 and 2023. Records were exported from Scopus, converted to CSV format, and analyzed in Bibliometrix, with VOSviewer used to visualize co-authorship, co-citation, and keyword co-occurrence networks. Results show a sustained increase in Scopus-indexed publications over the decade, indicating expanding scholarly attention to local politics as a dynamic arena shaped by governance arrangements, participation, accountability, and actor–policy interactions. This study contributes a replicable workflow and a trend map that can guide researchers in positioning future studies and help practitioners identify evidence clusters and gaps. A key limitation is reliance on Scopus only, which may underrepresent non-indexed and regional scholarship.